IMPACTO DE LA VARIABILIDAD CLIMÁTICA SOBRE LA RECARGA A LOS ACUÍFEROS EN LA CUENCA DEL RÍO POÁS, VALLE CENTRAL, COSTA RICA - Vargas, Asdrúbal (2011)
We analyzed the impact of climate variation over the distribution of the hydric resources in ríoPoás watershed. Monthly hydric balances were carried out through the period 1976-2001. It is possible to identify humid subperiods and a dry one, lasting each of them about 7 years. During the dry subperiod, annualrecharge reaches 1000 mm.In 1986 it was recorded 2019 mm rainfall, the lowest in the watershed, which is 22% less than the average;potential recharge was 36% lower (850 mm), and runoff, 32% lower. The highest rainfall was recorded in 1996,with 3646 mm, 40% higher than the average, potential recharge was 65% higher (2205 mm), and runoff, 30%higher than the average ones. It is considered that between 24 and 48% of precipitation becomes potentialrecharge and most of it occurs during September and October.There are stratigraphic and paleontological evidences that demonstrate climatic changes in the past. Thosechanges altered precipitation and temperature conditions, and therefore the distribution of water resources, with-out any anthrropic influence.